Free Vibration Response Of Double-Bay Multi-Storey Building Frames With Stiffened Joints (International Journal of Engineering and Computer Science, 2017)
This paper investigated self-excited vibration response of double-bay multi-storey building frames for the effect of joint stiffening on natural frequencies. One of the frames has normal rigid joints. Three others of the frames have stiffened joints of stiffened lengths: 250mm, 400mm and 750mm respectively. On account of limitations of shear frame models, the frames are modeled as frames with flexible horizontal members having multi degrees of freedom (MDOF). Classical displacement method of analysis is adopted using stiffness coefficients which are modified to include and embrace the contributions of joint stiffening. Results revealed: joint stiffening increased the natural frequencies of the frame; natural frequencies also increased with the length of stiffening. In addition, joint stiffening brought about enhanced values of other dynamic characteristics of the frame which are functions of natural frequencies.